Coronary microvascular dysfunction assessed by continuous intracoronary thermodilution: A comparative study with index of microvascular resistance. (15th June 2021) - Rivero, Fernando; Gutiérrez-Barrios, Alejandro; Gomez-Lara, Josep; Fuentes-Ferrer, Manuel; Cuesta, Javier; Keulards, Danielle C.J.; Pardo-Sanz, Ana; Bastante, Teresa; Izaga-Torralba, Elena; Gomez-Hospital, Joan-Antoni; García-Guimaraes, Marcos; Pijls, Nico H.J.; et al.
Abstract: Background: This study aimed to assess the correlation between the standard of care, the index of microvascular resistance (IMR) versus the novel microvascular resistance (Rmicro ) and to determine the pathologic cut-off value in a selected population with suspected coronary microvascular dysfunction (CMD). Methods: One-hundred and twenty patients with high clinical suspicion of CMD due to ischemic symptoms in the absence of significant epicardial coronary lesions were prospectively included. Following a standardized systematic protocol, coronary flow reserve, IMR, fractional flow reserve, Q and Rmicro were measured in the left anterior descending coronary artery using a temperature/pressure sensor-tipped guidewire and a dedicated infusion catheter. Results: There was a high prevalence of CMD with 50 (42%) patients showing an IMR ≥ 25. Median IMR was 23 [IQR: 14–34] and median Rmicro was 464 Woods Units (WU) [IQR: 354–636WU]. ROC analyses identified 500 WU as the optimal Rmicro cut-off to identify patients with an IMR ≥ 25, with an area under the ROC curve (C statistic) of 0.83 (95% CI: 0.74 to 0.89, p < 0.0001). Conclusions: Rmicro derived from continuous intracoronary thermodilution is an accurate index to measure microvascular resistances enabling the invasive diagnostic of CMD. Highlights: The presence of coronary microvascular dysfunction can be accurately diagnosed by measuring the minimum microvascular resistance obtained by the continuous thermodilution method. We found that a continuous thermodilution resistance value >500 WU predicts the presence of coronary microvascular dysfunction.